Procedure Costs of Peripheral Nerve Graft Reconstruction. Issue 4 (10th April 2023) - Raizman, Noah M.; Endress, Ryan D.; Styron, Joseph F.; Emont, Seth L.; Cao, Zhun; Park, Lawrence I.; Greenberg, Jeffery A.
Abstract : Background: Peripheral nerve injuries not repaired in an effective and timely manner may lead to permanent functional loss and/or pain. For gaps greater than 5 mm, autograft has been the gold standard. Allograft has recently emerged as an attractive alternative, delivering comparable functional recovery without risk of second surgical site morbidities. Cost is an important factor when considering surgical options, and with a paucity of nerve repair cost data, this study aimed to compare allograft and autograft procedure costs. Methods: A retrospective cross-sectional observational study using the US all-payer PINC AI Healthcare Database examined facility procedure costs and cost drivers in patients undergoing allograft or autograft repair of an isolated single peripheral nerve injury between January 2018 and August 2020. Inpatient repairs were limited to nerve-specific DRGs. Multivariable regression evaluated risk-adjusted procedure cost differences. Results: Peripheral nerve graft repairs (n = 1363) were more frequent in the outpatient setting, and more than half involved the use of allograft nerve. Procedure costs for allograft and autograft repair were not significantly different in the outpatient ( P = 0.43) or inpatient ( P = 0.71) setting even after controlling for other risk factors. Operating room cost was significantly higher for autograft in outpatient ( P < 0.0001) but not inpatient ( P = 0.46), whereas allograft implant cost was significantly higher in both settings ( P < 0.0001). Conclusions: No significant differences in procedure costs for autograft and allograft repair in inpatient and outpatient settings were found using real-world data. Future research should explore longer-term costs.